Implementing Head and Neck Contouring Peer Review without Pathway Delay: The On-demand Approach. Issue 12 (December 2017) - Fong, C.; Sanghera, P.; Good, J.; Nightingale, P.; Hartley, A.
Abstract: Aims: Peer review of contour volume is a priority in the radiotherapy treatment quality assurance process for head and neck cancer. It is essential that incorporation of peer review activity does not introduce additional delays. An on-demand peer review process was piloted to assess the feasibility and efficiency of this approach, as compared with a historic scheduled weekly approach. Materials and methods: Between November 2016 and April 2017 four head and neck clinicians in one centre took part in an on-demand peer review process. Cases were of radical or adjuvant intent of any histology and submitted on a voluntary basis. The outcome of contour peer review would be one of unchanged (UC), unchanged with variation or discretion noted (UV), minor change (M) or significant change (S). The time difference between the completion of the on-demand peer review was compared with the time difference to a hypothetical next Monday or Tuesday weekly peer review meeting. The time taken to review each case was also documented in the latter period of the pilot project. Results: In total, 62 cases underwent peer review. Peer review on-demand provided dosimetrists with an average of an extra two working days available per case to meet treatment start dates. The proportion of cases with outcomes UC, UV, M and S were 45%, 16%, 26% and 13%, respectively. The mean peer review time spent per case was 17 min (12 cases). The main reason for S was discrepancy in imaging interpretation (4/8 cases). A lower proportion of oropharyngeal cases were submitted and had S outcomes. A higher proportion of complex cases, e.g. sinonasal/nasopharynx location or previous downstaging chemotherapy had S outcomes. The distribution of S outcomes appears to be similar regardless of clinician experience. The level of peer review activity among individuals differed by workload and job timetable. Conclusion: On-demand peer review of the head and neck contour volume is feasible, reduces delay to the start of dosimetry planning and bypasses the logistical barriers of weekly meetings. An audit of participation will be required to ensure successful implementation. Highlights: On-demand contour peer review bypasses logistical barriers of weekly meetings. Dosimetrists gained on average extra two working days to meet treatment start dates. Imaging interpretation accounts for the majority of significant contour changes. Time allocation and audit of participation required for successful implementation.